Clube de ciências como espaço de desenvolvimento das competências para ensinar : uma análise à luz da teoria de Philippe Perrenoud - Gonçalves, Tatiane Alves (2020)
The purpose of this investigation was to analyze the development of teaching skills expressed by teachers who work in Science Clubs. This research is a qualitative study case. Interviews were conducted with four working teachers in science clubs at private schools in the southern region of Brazil. The analysis for obtained data was carried out through the Textual Discursive Analysis. The meetings in these spaces, are held during school hours on a specific day of the week. Based on the teachers' reports about their performances in the science clubs, it was possible to identify many of the competences professed by Perrenoud, as well as these non-formal spaces contribute to the professional teachers’ development. Further on, it was found that reproductions of experiments and transmissive activities do not occur in the investigated clubs. The adopted pedagogies allow the socialization of knowledge in a significant way among teachers, club members and monitors. In addition to addressing subjects that can be chosen by students, the work done through learning units makes it evident that the teaching development skills is fundamental to the citizens’ formation who think critically and who can be motivated to change the reality around them.